(untitled) (Balneo and PRM Research Journal, 2024)
The subtleties involved in the post-surgical recovery of people suffering from spinal cord injuries involve notable psychological issues that require further examination. (1) Background: people affected by spinal cord injuries may experience severe symptoms, as motor skill deficits, sensory processing irregularities, and pain, all of which can have a negative impact on their quality of life and mental health.; (2) Methods: we studied 264 patients hospitalized in the Neurosurgery Clinic 2 of the "Bagdar Arseni" Hospital for acute spinal cord injuries, in 2 groups of patients with and without CBT psychotherapy; (3) Results: we studied 97 women and 167 men; average anxiety was lower in women compared to men, showing a decreasing trend after psychotherapy for both sexes (4) Conclusions: we discovered that anticipatory anxiety after spinal cord injuries is high, especially in male patients. And psychotherapy brings benefits in reducing anxiety for both categories of patients, regardless of the age group they belong to.